Patient preferences and attitudes towards first choice medical services in Shenzhen, China: a cross-sectional study. Issue 5 (24th May 2022) - Zhao, Xinyu; Xiao, Junhui; Chen, Huida; Lin, Kena; Li, Xiaoman; Zeng, Zhiwen; Huang, Shuyun; Xie, Zhikui; Du, Jinlin
Abstract : Objective: This study aimed to explore the characteristics of Shenzhen residents' preferences and influencing factors regarding their first choice of medical institution at various medical levels, and to understand their attitudes towards community health services. Design: Cross-sectional survey. Participants: A total of 1612 participants at least 18 years of age were randomly sampled with stratification among 10 districts in Shenzhen. Data were gathered through a self-designed questionnaire. The effective questionnaire response rate was 93.05%. All patients participated in the study voluntarily, provided written informed consent and were able to complete the questionnaire. Main outcome measures: We measured and compared the participants' expected and actual preferences and influencing factors regarding their first choice of medical service at various medical levels. Results: More than 50% of the participants preferred municipal and district hospitals as their first choice, and 27.5% chose medical institutions according to specific circumstances. Univariate analysis indicated that age, education, income, medical insurance, housing conditions and registered permanent residence were significantly associated with the actual and expected preferred first medical institution. The main factors influencing participants' actual and expected preferred medical institution differed. With the actual preferred first medical institution as the dependent variable, education, monthly income, medical technology, convenience and providers' service attitude and medical ethics were the main factors (χ 2 =212.63, p<0.001), whereas with the expected preferred first medical institution as the dependent variable, occupation, Shenzhen registered permanent residence, education and medical technology were the main factors (χ 2 =78.101, p<0.001). Conclusion: The main factors influencing participants' preferred medical institution and their actual first visit differed. Patients with high education or income or registered permanent residence preferred high-level medical institutions for the first visit.